Olfatory HLA-associated mechanism of formation of married couples in the development of congenital heart diseases in children - A. A. Chuyanova; A. V. Sinitskaya; N. A. Litvinova (Acta Biomedica Scientifica, 2022)
Taking into account the significance of the HLA complex in the inflammatory and immune responses, we can assume that the potential for limiting or developing pathology in the next generation will be determined at the stage of selection of certain alleles in the spousal genotype.The aim. To study the role of HLA assortativity in couples with healthy children and couples with children with congenital heart diseases (CHD) through the prism of immunogenetic mechanisms of mutual olfactory choice.Materials and methods. We studied the distribution of HLA-DRB1 alleles in married couples with healthy children and with children having CHD. To identify the associations of HLA-DRB1 alleles with odor preferences, we also studied the group included young males and females. HLA-DRB1 gene typing was carried out in all participants.Results. The combination of HLA-DRB1 alleles in couples with healthy children was similar to the combination of these alleles in the mutual olfactory sympathy between unfamiliar young males and females. Allele combinations in the spouses from the experimental group differ from the group of random selection. The frequency of matches for HLA-DRB1 alleles in married couples with children having CHD without was significantly higher than in the control group.Conclusion. The first stage of selection, associated with olfactory selection, is aimed to the whole population, and it is significantly manifested in the control group (married couples with healthy children). At the same time, in the experimental group (couples with children having CHD), some deviations from the main selection were discovered. Generally, specific HLA-DRB1 allele combinations obtained on the basis of olfactory assessments, indicate the involvement of HLA molecules in pheromone reception.